SESENGGAK DALAM BAHASA SASAK: CITRAAN METAFORIS DAN SIGNIFIKANSINYA - Saharudin Saharudin (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
The aims of this research are to describe the metaphorical image in sêsênggak (Sasak proverbs) which is based on the types of reference as the target domain (tenor) and source domain (vehicle); and to uncover the meaning or significance. The data are collected through participant observation method and in-depth interview with key informants. The results show, on one hand, that the sociocultural background of the Sasak community gives the most dominant contribution in sêsênggak’s lexicon (language). On the other, that socio-cultural background has much mpression on the various humanitarian issues involving sêsênggak, which is created to control (directive-prohibitive) and to evaluate the attitude or behavior of a person or a certain group of people. On that ground, sêsênggak was born from some unique mixtures of the natural environment and the socio-cultural organization of thoughts, opinions, memories, senses, experiences, knowledge, imaginations, creativities, sensitivities, intelligences, as well as consciousness, which are based on the rules, the laws, and the societal structures. These mixtures become a united, coherent, rational, and organized expression in the framework of language and conscience.